Answer:
a2=12 (the second term of the sequence is 12)
Step-by-step explanation:
a5=324
If the term to term rule is multiply by any number, we deal with geometrical sequence
The formula you should use is an= a1*r^(n-1) where n is the number of the term which we know. In our case we know
a5, so use 5 instead of n
Then you have a5=a1*r^4 where r is the number 3 (because each next term is greater than previous in 3 times)
a5=324
324= a1*3^4
324=a1*81
a1=4 (We find the first term of sequence, because having it you can easily search for every term )
Return to the formula an= a1*r^n-1
Now search for the second term using 2 instead of n in the formula
a2= a1*r^1
a2=a1*r, a1=4, r=3
a2=4*3=12
Step-by-step explanation:
x^2/9 z^2
hiiii checkout the steps
Answer:
3.77
Step-by-step explanation:
Do 13.85-9.08 and
u get 3.77
Answer:
2x^2 +11
Step-by-step explanation:
f(x) = 3x^2 +2
g(x) = x^2 -9
f(x) - g(x) = 3x^2 +2 - (x^2 -9)
Distribute the minus sign
= 3x^2 +2 -x^2 +9
Combine like terms
= 2x^2 +11